Wartość wychowania w rodzinie luterańskiej w piśmiennictwie staropolskim XVI i XVII wieku - Nowicki , Michał (Studia Edukacyjne, 2019)
The article deals with the issue of the value of upbringing in the Lutheran family as shown in the Old Polish literature of the 16th and 17th centuries. The first of the two parts discusses the formation of Lutheran educational thought in the context of the development of modern culture, reforms of Martin Luther and the work of Philip Melanchthon. The second part demonstrates the reception of these views in Polish pedagogical texts. In these texts, several features specific to the Protestant perspective can be distinguished. First of all, it is a strongly emphasized fear of God, a significant role of the father in the upbringing of not only children but also the whole family together with the retinue (following the example of the Roman tradition), and a rather poorly emphasized woman’s role in the family (only in the context of her maternal function in the period of necessary care for children). Particular importance was attached to the family itself as an institution established by God, to parenthood and the need to carefully educate offspring, to the personal involvement and efforts of both parents to educate their children.